A comparative study of two surgical management methods for cervical incompetence at the University College Hospital, Ibadan (2007)
Incompetence of the internal uterine cervical os is associated with recurrent pregnancy loss. Different surgical techniques are in practice to correct the defect. The objective of this study therefore was to review the outcome of pregnancies following cervical using either of the two procedure among patients diagnosed as having incompetence of the cervix. A comparative study of 2 standard methods of cerclage used in our hospital, McDonald & Shirodkar, in a group of 80 patients was done. All the patients had cervical cerclage insertion done between the 14 & 16 weeks of gestation using either of the two methods. There was no significant morbidity with either of the 2 methods. The overall success rates, as measured by continuation of the pregnancy to term, were similar. Both methods of cervical cerclage are equally effective in producing the desired outcome, but since the McDonald method is technically simpler to perform, it may be desirable to adopt this approach more frequently.